2021
DOI: 10.1039/d0qi01140a
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the structure–property relationship of UO2nanoparticles

Abstract: We show that the structural and electronic properties of UO2 NPs (2–3 nm) are similar to those of bulk UO2 under inert conditions, with U(iv) as the dominating oxidation state, though NPs oxidize with time and under the X-ray beam.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…It was shown that the PuO 2 NPs remain intact after several months 63 with respect to the size (~2nm) and oxidation state 63 . Contrary to that, the UO 2 NPs increase in size up to ~6nm and become partially oxidized with time even if the samples were kept under inert conditions 66 . It was found that the U(V) signal increased and a conversion to the U 4 O 9 phase took place.…”
Section: Oxidation State Verificationmentioning
confidence: 85%
See 3 more Smart Citations
“…It was shown that the PuO 2 NPs remain intact after several months 63 with respect to the size (~2nm) and oxidation state 63 . Contrary to that, the UO 2 NPs increase in size up to ~6nm and become partially oxidized with time even if the samples were kept under inert conditions 66 . It was found that the U(V) signal increased and a conversion to the U 4 O 9 phase took place.…”
Section: Oxidation State Verificationmentioning
confidence: 85%
“…The actinide M 4,5 HERFD-XANES method gives the opportunity to fingerprint the oxidation state of the actinidecontaining materials. The first U M 4 experiment has been done on the mixed uranium oxides 3 , which was followed by several other Please do not adjust margins Please do not adjust margins studies on the chemical state verification in actinide systems 3,6,9,12,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] . Fig.…”
Section: Oxidation State Verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…[46][47][48][49][50][51] XANES at the metal L and M edges is also used in Ln and An chemistry research. 26,36,[52][53][54][55][56][57][58][59][60][61][62][63][64][65] The L edge probes dipole-allowed 2p → nd transitions and also provides information about the fshell occupation. The (relative) intensity between the spectral features, and the energy of the main edge, are very sensitive to the metal oxidation state and f-electron count.…”
Section: Introductionmentioning
confidence: 99%